Thoracic Injuries in Pediatric Polytraumatized Patients: Epidemiology, Treatment and Outcome. Issue 6 (June 2021) - Ostermann, R.C.; Joestl, J.; Lang, N.; Tiefenboeck, Thomas M.; Ohnesorg, Sylvina; Platzer, P.; Hofbauer, M.
Highlights: severity of concomitant chest injuries in polytraumatized pediatric and adolescent patients contributes substantially to morbidity and mortality Physicians have to be aware of chest injuries also in the absence of rip fractures Significant chest injuries without rib fracture were frequent Abstract: Purpose: The purpose of the present study was to assess the influence and contribution, epidemiology, treatment and outcome of thoracic injuries in a cohort of pediatric and adolescent polytraumatized patients. Material and Methods: All pediatric and adolescent (age < 18 years) polytraumatized patients with associated thoracic injuries were included in this study. Demographic data, mechanism of injury (MOI), injury severity score (ISS), Glasgow Coma Scale (GCS), hemodynamic parameters and pupillary response at ED admission, site of major injury (SOMI), associated chest and non-chest related injuries, length of hospital stay (LOS), procedures performed at the ED as well as outcome variables including mortality and cause of death. Stepwise logistic regression analysis was used to identify risk factors for a poor prognosis and outcome. Results: The logistic regression found the following variables decreasing the odds for a "bad outcome": lack of a hemodynamically unstable condition (p = 0.009) and the absence of a pathological pupillary response (p < 0.001). Conclusions: The present study suggests that the severity of concomitant chest injuries in polytraumatized pediatric and adolescent patients contributes substantially to morbidity and mortality. Due to the anatomic features of the immature pediatric bones, careful attention should be drawn to possible severe chest injuries even in the absence of rib fractures. Level of evidence: A retrospective study (level – IV study)